4 - Policing Looted Funds with the Whistle: Newspaper Coverage of the Anti-corruption Crusade in Nigeria - Tade, Oludayo (Africa Development, 2019)
This article examines the Whistle Blowing Policy (WBP) in Nigeria’s anti-corruption crusade between 2016 and 2017. It seeks to understand how looters innovate to keep loots, following the implementation of this policy, and the extent to which looting undermines governance and amplifies insecurity. This is vital as the perception of Nigerian corruption globally has been dismal in the last five years. Corruption slackens development and becomes a major security threat in Nigeria, as collective patrimony/public monies are siphoned or diverted into private pockets. Relying on newspaper data on coverage of corruption, this article argues that ‘incentivising patriotism’ through the WBP has contributed to citizens’ participation in the anti-corruption crusade in Nigeria and enhanced recoveries of illicitly acquired monies. The policy has forced looters to adopt traditional money-keeping strategies to keep looted monies in private fortes, septic-tanks, stores, and/or to abandon the same in airport and market shops. The article concludes by showing the value of what the recovered looted monies could have done to enhance governance and development, to underscore how illicit monies undermine security and democratic governance in Nigeria.